2018
DOI: 10.1177/1403494818812638
|View full text |Cite
|
Sign up to set email alerts
|

Can a poor psychosocial work environment and insufficient organizational resources explain the higher risk of ill-health and sickness absence in human service occupations? Evidence from a Swedish national cohort

Abstract: Aim: The aim of this study was to investigate differences in burnout, self-rated health (SRH) and sickness absence between human service occupations (HSOs) and other occupations, and whether they can be attributed to differences in psychosocial work environment and organizational resources. Methods: Data were derived from the Swedish Longitudinal Occupational Survey of Health, an approximately representative sample of the Swedish working population (n = 4408). Employment in HSOs, psychosocial work environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 25 publications
3
33
0
3
Order By: Relevance
“…Data on the participants' occupations were based on the Swedish Standard Classification of Occupations (SSYK 2012) and obtained from register data. We used the same definition of HSO, developed in collaboration with several Swedish authorities, as in a previous publication (2). In accordance with this definition we categorized "occupations in which contact with children, students, sick, older adults, or individuals with a vulnerable societal position is part of the daily work tasks" into HSO.…”
Section: Human Service Occupationmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the participants' occupations were based on the Swedish Standard Classification of Occupations (SSYK 2012) and obtained from register data. We used the same definition of HSO, developed in collaboration with several Swedish authorities, as in a previous publication (2). In accordance with this definition we categorized "occupations in which contact with children, students, sick, older adults, or individuals with a vulnerable societal position is part of the daily work tasks" into HSO.…”
Section: Human Service Occupationmentioning
confidence: 99%
“…A large number of the Swedish workforce, particularly women, are employed in occupations in which contact with children, students, sick, or older people is part of the everyday work tasks (1). It has in recent years been acknowledged that employees in these so-called "human service occupations" (HSO) have increased risks of mental ill-health and sickness absence compared with other occupations on the Swedish labor market (1,2). Several possible reasons for this increase have been suggested, such as poorer working conditions in these professions (2) and a higher total burden of emotionally demanding work from paid and unpaid work together (3).…”
mentioning
confidence: 99%
“…A Swedish study concluded that increasing WTC for those with low levels of control could result in a reduction up to 12% in SA (more than 30 days), depending on the type of occupation. 11 Differential effects of the two sub-dimensions of WTC on health outcomes are rarely investigated. 12 In a previous study, we found control over time off to be more strongly associated with depressive symptoms than control over daily hours.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ala‐Mursula et al (2002) found that, for women, low WTC increased risk of SA of more than 3 days. A Swedish study concluded that increasing WTC for those with low levels of control could result in a reduction up to 12% in SA (more than 30 days), depending on the type of occupation 11 …”
Section: Introductionmentioning
confidence: 99%
“…However, the etiology of SA is often multifactorial which makes it difficult to comprehend and requires a holistic understanding (10)(11)(12). Many factors have been associated with an increased LTSA risk, for example, age, gender, lifestyle, poor health, SA records, physical workload, and psychosocial working conditions (10,(13)(14)(15). Therefore, individual or indicated prevention might result in better outcomes since it focuses on a broad range of potentially interrelated factors, in contrast to population or general prevention, which is often restricted to one or two factors.…”
mentioning
confidence: 99%